2022
DOI: 10.1155/2022/2755332
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of Traditional Chinese Medicine Therapy for Type 2 Diabetes Mellitus: An Evidence Map

Abstract: Type 2 diabetes mellitus (T2DM), a common disease with a complex etiology in the world, is an important risk factor for severe cardiovascular and cerebrovascular diseases. However, treatments of T2DM are mainly based on Western medicine, whose severe side effects make traditional Chinese medicine (TCM) therapy more appealing to patients and clinicians. The overall clinical evidence for different TCM therapies in the treatment of T2DM is still unclear. This study aimed to adopt the evidence-mapping method and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In addition, the safety profile of HJD was also assessed in this meta-analysis. The results showed that HJD did not increase the risk of adverse events, and importantly, HJD combination therapy did not increase the incidence of diarrhea, which is often a concern with herbal formulations [61]. This finding highlights the potential of HJD as a safe adjunctive therapy for T2DM.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, the safety profile of HJD was also assessed in this meta-analysis. The results showed that HJD did not increase the risk of adverse events, and importantly, HJD combination therapy did not increase the incidence of diarrhea, which is often a concern with herbal formulations [61]. This finding highlights the potential of HJD as a safe adjunctive therapy for T2DM.…”
Section: Discussionmentioning
confidence: 95%
“…The global epidemic of T2DM is an alarming cause of mortality and disability. Some physicians agree that herbal medicine and its formulations are safe and useful in treating persons with T2DM in many countries ( 48 50 ). The aim of our study was to evaluate the adjuvant hypoglycemic effect of jinlida granules in the treatment of T2DM and to explore the source of heterogeneity between these RCTs.…”
Section: Discussionmentioning
confidence: 99%
“… 6 In recent decades, a series of clinical studies have confirmed that traditional Chinese medicines play an essential role in the treatment of T2DM. 7 Quercetin, a flavonoid antioxidant, is a bioactive component of various Chinese traditional medicines with ideal medicinal value. 8 Various studies have demonstrated that quercetin produces a protective effect on diabetes by preserving pancreatic islet morphology and β-cell numbers or promoting insulin secretion.…”
Section: Introductionmentioning
confidence: 99%